(untitled) (Global Journal of Medical Research, 2014)
Background: Acute appendicitis is one of the commonest causes of acute abdomen. Several studies have looked at the role of C-reactive protein (CRP) and white cell count (WCC) in diagnosing acute appendicitis with varying results but there is a scarcity of such data in the U.A.E. The aim of this study was to determine the sensitivity and specificity of CRP, WCC and neutrophils count in the diagnosis of acute appendicitis. Methods: The study was carried out between December 2011 and December 2012. This was a prospectively conducted, retrospectively analyzed study. 535 patients underwent appendicectomy during the study period (418 laparoscopic and 117 open appendicectomies). Two hundred and forty nine patients were eligible for inclusion in the final analysis. The patients preoperative CRP, WCC and Neutrophils count were measured and compared to the histopathology of the appendix which was grouped into either positive or negative for appendicitis.